2015
DOI: 10.1051/0004-6361/201425334
|View full text |Cite
|
Sign up to set email alerts
|

Faint AGNs atz>4 in the CANDELS GOODS-S field: looking for contributors to the reionization of the Universe

Abstract: Context. Establishing the number of faint active galactic nuclei (AGNs) at z = 4−6 is crucial to understanding their cosmological importance as main contributors to the reionization of the Universe. Aims. In order to derive the AGN contribution to the cosmological ionizing emissivity we have selected faint AGN candidates at z > 4 in the CANDELS GOODS-South field, which is one of the deepest fields with extensive multiwavelength coverage from Chandra, HST, Spitzer, and various ground-based telescopes. Methods. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
607
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(665 citation statements)
references
References 83 publications
(111 reference statements)
40
607
18
Order By: Relevance
“…We see that the model shows good agreement with observations across a large redshift range (z ∼ 6 − 0.6). At high redshift the model is consistent with the samples of bright quasars (Willott et al 2010;Shen & Kelly 2012;McGreer et al 2013;Jiang et al 2016) while it predicts a lower number density of faint quasars compared to the Giallongo et al (2015, hereafter the G15) sample. On the other hand, the model produces a significant number of faint quasars.…”
Section: Quasar Luminosity Functionsupporting
confidence: 73%
See 1 more Smart Citation
“…We see that the model shows good agreement with observations across a large redshift range (z ∼ 6 − 0.6). At high redshift the model is consistent with the samples of bright quasars (Willott et al 2010;Shen & Kelly 2012;McGreer et al 2013;Jiang et al 2016) while it predicts a lower number density of faint quasars compared to the Giallongo et al (2015, hereafter the G15) sample. On the other hand, the model produces a significant number of faint quasars.…”
Section: Quasar Luminosity Functionsupporting
confidence: 73%
“…With a high escape fraction (fesc,q ∼ 1, , quasars (AGN) are potential contributors to reionization (Volonteri & Gnedin 2009;Fontanot et al 2014;Madau & Haardt 2015;Mitra et al 2015), despite their relatively low number. Recently, Giallongo et al (2015) identified faint AGN candidates in the CANDELS GOODS-South field and suggested that there is a high number density of faint AGN at z = 4 − 6. These faint quasars provide a new source of reionization (Madau & Haardt 2015).…”
Section: Introductionmentioning
confidence: 99%
“…10), the BH luminosity function of this model is the closest to the bolometric and X-ray luminosity functions derived respectively by Hopkins, Richards & Hernquist (2007), and Buchner et al (2015) (Fig. 12), and finally the model provides a number of AGN in better agreement with the number of AGN candidates detected in the CDF-S survey (Giallongo et al 2015) at high redshift. Figure 13.…”
Section: Low Redshift Analogues Of High Redshift Galaxiessupporting
confidence: 72%
“…The contribution of quasars are incorporated here based on their observed luminosity function at z < 6 (Hopkins et al 2007) and they have insignificant effects on IGM at higher redshifts (but also see Giallongo et al 2015;Madau & Haardt 2015). Furthermore, the model calculates the suppression of star formation in low-mass haloes (radiative feedback) through a Jeans mass prescription, which is computed self-consistently from the evolution of the thermal properties of IGM through the minimum circular velocity of haloes that are able to cool (Choudhury & Ferrara 2005; also comparable to the simulations by Okamoto et al 2008;Sobacchi & Mesinger 2013).…”
Section: Data-constrained Reionization Modelmentioning
confidence: 99%